Investigating the Protective Effects of Rutin on Cholemic Nephropathy in Cholestatic Rats - Zeynab Jashni; Mohammad Ghaffari Nasab; Iraj Salimi Kia; Alimohammad Maleki; Soosan Abdollahi; Hamidreza Mohammadi (Journal of Mazandaran University of Medical Sciences)
Background and purpose: Hepatic cholestasis is a primary cause of liver failure and can lead to complications in other organs, including the kidneys. Kidney damage resulting from liver dysfunction is known as cholemic nephropathy. Oxidative stress is a key mechanism in causing this damage. Oxidative stress occurs when the ratio of free radicals to antioxidant enzymes is imbalanced, with free radicals prevailing. Medicinal plants are often used to treat and prevent diseases due to their antioxidant properties. Rutin (ROT), a bioflavonoid with antioxidant properties found in certain foods, may offer protective effects. Therefore, this study aimed to investigate the protective effect of rutin on kidney damage following hepatic cholestasis in rats. Materials and methods: This experimental study included 50 Wistar rats, randomly divided into 5 experimental groups (n=10). Cholestasis was induced by ligating the common bile duct. Rutin was administered daily via gavage in different doses (30, 60, and 120 mg/kg) to the affected rats for 14 days. At the end of the intervention, the animals were anesthetized, tissue samples were collected, and serum and urine samples were obtained for further testing. Antioxidant enzyme activities, including catalase (CAT), superoxide dismutase (SOD), and glutathione peroxidase (GPx), were measured in kidney tissue homogenates using an ELISA kit, following the manufacturer’s instructions. For assessing reactive oxygen species (ROS) and malondialdehyde (MDA) levels, 500 mg of kidney tissue was homogenized in 5 ml of cooled KCl solution. The protective effects of rutin were evaluated by analyzing serum biochemical factors (BUN and creatinine), urine parameters (glucose and protein), oxidative stress markers (ROS and MDA), and antioxidant enzyme activities (GPx, SOD, and CAT). Statistical analysis was performed using GraphPad software, with one-way ANOVA and Tukey’s test. Results: The study results showed that, following cholestasis induction, urinary biochemical factors (glucose and protein) significantly increased. However, rutin treatment significantly reduced urinary glucose and protein excretion (P<0.05). Additionally, in cholestatic animals, serum biochemical factors (BUN and creatinine) increased markedly compared to the control group, but following rutin administration, these biomarker levels significantly decreased compared to the cholestatic group (P<0.05). Oxidative stress marker analysis revealed that ROS and MDA levels were significantly elevated in the kidney tissues of cholestatic animals compared to controls; rutin treatment significantly reduced these levels in the treated group compared to the cholestatic group (P<0.05). Furthermore, GPx, CAT, and SOD enzyme activities were significantly reduced in the cholestatic group, but after rutin administration, these enzyme activities significantly increased compared to the cholestatic group (P<0.05). Conclusion: The present study demonstrates that rutin administration, at various doses, had a beneficial effect in reducing serum and urinary factors and oxidative stress markers while enhancing antioxidant enzyme activity in kidney damage resulting from chronic liver failure.